Attitudes and behaviors towards mental illness of pre-service teachers in educational sciences - DARJAN Ioana; LUȘTREA Anca (Revista de Știinţe Educaţiei, 2018)
The personal system of beliefs and attitudes influence emotional and behavioral reactions. In educational field, teachers’ systems of beliefs, their set minds are of extreme importance, as they will direct and impact on their classroom practices, relational and instructional approaches. The pre-service teachers in Educational Sciences will become qualified professionals in educational field, in all its forms: mainstream, special, and integrated education. The future teachers face an extremely fluid educational environment, in terms of students’ characteristics, educational objectives, both academic and social, instructional and formative needs. With an increasing rate of school inclusion of students with Special Educational Needs (SEN) (Horga, 2016), the future specialists should be prepared, in terms of competences, to promote and sustain inclusion, to act against discrimination and exclusion, to advocate for the rights of all their students. Aiming to prepare highly qualified education specialists, it is important to assess their attitudes and positions towards students with diverse special needs, from diverse special contexts. As future specialists in education, our pre-service teachers will work directly with students with special needs and their families and will represent important agents in changing mentalities and generating adequate attitudinal and behavioral changes. In this study, we investigate our pre-service teachers’ the knowledge, attitudes and behaviors towards mental illness. A survey questionnaire covering topics as knowledge, attitudes and behavior towards people with mental illness was administrated to 82 of our pre-service teachers. The study presents the findings and the conclusions of the survey.